KEPUASAN KONSUMEN DALAM BELANJA SAYURAN SECARA ONLINE DI PO. ELLFAZ FRUITS & VEGETABLES DI KECAMATAN BANDUNGAN - Febryanna Savitri; Bayu Nuswantara (Universitas Galuh, 2022)
Currently online shopping is becoming a populer way among the public, this can be seen by the development of the process of buying and selling vegetables online that makes it easier for consumers to buy vegetables. Consumers can shop anytime and anywhere easily. The purpose of this study is to find out the characteristics of vegetable consumers to satisfaction in shopping vegetables online and know the level of satisfaction based on the dimension of consumer satisfaction. The research method used is quantitative descriptive research with purposive sampling techniques as many as 60 respondents of PO Ellfaz Fruits &Vegetables PO consumers. With data analysis techniques used are CSI (Customer Satisfaction Index) method and IPA (Importance Performance Analysis) method. The results of this study show that freshness aribut should be prioritized to be improved so that the performance of these attributes increases and meets consumer expectations.